Immune Responses in Mice Immunized with Mastitis Multiple Vaccines Using Different Adjuvants - Zhang, Zhe; Li, Xin-Pu; Yang, Feng; Luo, Jin-Yin; Wang, Xu-Rong; Liu, Long-hai; Li, Hong-Sheng (Acta Scientiae Veterinariae, 2018)
Background: Bovine mastitis, a serious disease associated with both high incidence and significant economic losses, posing a major challenge to the global dairy industry. The development of vaccines for protection from new infections by mastitis pathogens is of considerable interest to the milk production industry. Vaccination is a common and easy strategy for the control of infectious diseases, and the adjuvants used in the formulation is a critical factor for vaccine efficacy improvement. The main objective of the present study was to evaluate three different adjuvants for their ability to enhance immune responses of mice that vaccinated with Bovine Mastitis Multiple Vaccine. Materials, Methods & Results: The thymus and spleen index, the phagocytic ability of macrophage and the serum antibody levels of mice were detected after vaccination, respectively. The results showed that the thymus index, spleen index, and the phagocytic ability of macrophage of mice in Aluminum group exhibited a significant higher level (P < 0.05) compared with those in the control groups. The difference of the serum antibody levels was significant (P < 0.05) between experimental groups and control group after vaccination. The serum antibody concentration of mice in FIA group was higher compared with other groups and had a longer duration. The antibody concentration of mice in France 206 oil group can not increase as fast as the antibody concentration of Aluminum group, but it can last a longer time at a high level. In conclusion, multiple vaccines mixed with three different adjuvants could enhance the immunity of mice and Freund’s incomplete adjuvant is the best choice for this vaccine. Discussion: Adjuvants play an important role in increasing the efficacy of a number of different vaccines. In this study, three kinds of adjuvants (Aluminum hydroxide, France 206 oil and FIA) were evaluated for their adjuvant effects for multiple vaccine of bovine mastitis in mice and aluminum hydroxide did best as the vaccine adjuvant from the results. Aluminum hydroxide is a universally accepted adjuvant for both human and veterinary vaccines. The goal of vaccination is to generate strong immune response providing protection against infection for a time. Different protective effects will usually obtained by different adjuvants even use same antigen. In this work, FIA, Alum and 206 oil were chosen as adjuvants for inactivated antigens of Streptococcus agalactiae, Streptococcus dysgalactiae and Staphylococcus aureus. The results showed that there was a significantly higher antibody levels in vaccinated mice compared with those in control group. In addition, the mice in France 206 oil and FIA group performed a higher antibody levels and stronger immunity than mice in Aluminum hydroxide groups. These findings suggest that Freund’s incomplete adjuvant (FIA) would be the best candidate as the adjuvant for mastitis multiple vaccines investigated in this study.